Integrating Modern Pedagogies into Islamic Education: Bridging Tradition with 21st-Century Innovation - Swani Dube; Karma Zheba (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This study critically explores the integration of modern pedagogical approaches into Islamic education, addressing a significant research gap concerning how classical teaching traditions can remain relevant and impactful in the context of 21st-century learning. Historically, Islamic pedagogy has been grounded in approaches such as talaqqi (direct transmission), hafalan (memorization), mudhakarah (dialogue), and tarbiyah (mentorship), all of which aim to cultivate discipline, spiritual depth, and ethical character. However, these approaches alone may not fully equip learners with the critical thinking, creativity, and digital literacy required by contemporary educational environments. Using a library-based descriptive–analytical synthesis, the study examines classical Islamic sources alongside modern educational theories. Literature was selected based on relevance to pedagogy, tradition, and innovation, and was triangulated across multiple scholarly perspectives. Findings demonstrate that integrating student-centred, project-based, collaborative, and technology-enhanced methods with traditional practices significantly enriches the quality and scope of Islamic education. Such integration produces learners who are intellectually capable, spiritually grounded, ethically responsible, and prepared to engage with global challenges. The study concludes that tradition and innovation are not mutually exclusive but mutually reinforcing, forming a comprehensive pedagogical framework that preserves Islamic epistemological and ethical foundations while responding effectively to the demands of contemporary education. Ultimately, this research advances Islamic pedagogy by offering a model for harmonising classical principles with innovative methodologies to cultivate insan kamil complete human beings who contribute positively to society.